A rare case of spontaneous rupture of an aneurysm of the right gastric artery. (2017) - Takemoto, Yu-ki; Fujikuni, Nobuaki; Tanabe, Kazuaki; Amano, Hironobu; Noriyuki, Toshio; Nakahara, Masahiro
Highlights: We report here a rare case of intra-abdominal bleeding from a ruptured aneurysm of the right gastric artery. Transcatheter arterial embolization (TAE) could not be adopted due to thrombotic occlusion of arteries, so we performed an urgent laparotomy. We should not hesitate to convert endovascular approach into a laparotomy in an emergency situation. Abstract: Background: Visceral artery aneurysms at the origin of the gastric and gastroepiploic artery are uncommon. Raptured visceral aneurysms cause high mortality and require urgent and adequate intervention and treatment. Presentation of case: A 65-year-old woman was transferred to the emergency department with sudden abdominal and back pain. Radiographically, we diagnosed intra-abdominal bleeding due to a ruptured aneurysm of the right gastric artery. Although her vital signs were relatively stable, transcatheter arterial embolization (TAE) could not be performed due to thrombotic occlusion of her abdominal aorta, and bilateral axillary arteries. She underwent an emergency laparotomy with ligation of the root of the right gastric artery and resection of the aneurysm, following which she showed good recovery. Histologically, the right gastric artery showed atherosclerosis with an organizing mural thrombus. Discussion: Ruptured visceral aneurysms cause high mortality; therefore, rapid and adequate treatment is necessary. Achieving adequate transcatheter access might be difficult in some cases. In our case, we performed an emergency laparotomy and had good recovery. Conclusion: We report and discuss the literature review for a rare case of intra-abdominal bleeding from a ruptured aneurysm of the right gastric artery which was difficult to be approache by TAE. In patients with unstable vital signs or in whom it is not possible to obtain a good laparoscopic view and clear operative field, we should not hesitate to convert the procedure into an open one, and perform an emergency laparotomy.